Características químicas de abacaxi 'Pérola' após tratamento com calor e armazenagem em três temperaturas - Souto, Rosilene Ferreira; Durigan, José Fernando [UNESP]; Santos, Leandra Oliveira [UNESP]; de Souza, Bianca Sarzi; Menegucci, João Luiz Palma (My University, 2010)
The effects of heating the fruits at 40°C for 24 hours and different storage temperatures (8oC, 14oC and 25oC, at 90% RH) to postharvest conservation of 'Pérola' pineapple fruit, harvested on pintado maturation stage. The evaluations were carried at the beginning (day 0), for initial characterization of the fruit and after 1, 5, 9, 13, and 17 days, with the fruit kept under refrigeration were transferred to environmental condition at 25°C and 75-80% RH and evaluated at the 21, 25, 29 days. It was used an entirely randomized experimental design, in a factorial scheme of 2x3x9, with fruit thermally treated or non-treated fruits, storage at 25oC, 14oC, and 8oC and 9 different evaluation periods. The fruit were evaluated for rottenness and pulp darkening incidence, pulp color and appearance, soluble solids (SS), titratable acidity (AT), soluble and reduced sugars and ascorbic acid content, besides SS/AT ratio. The results indicate that the pulp color became yellower during the refrigerated period, while the titratable acidity increased. During this period, the SS/AT rate lowered, but increased when the fruit were transferred to the environment, while the soluble and reduced sugars content decreased initially, before stabilizing. The ascorbic acid content had no significant variations, but showed a tendency of increasing. The fruit kept under environmental conditions did not show signs of chilling injury that were observed in the fruits after 8 days at refrigeration, after being taken out to the environmental conditions, with greater intensity in those thermally treated fruits.
Pineapple 'Pérola' chemical characteristics after rot treatment and storage in three temperature
Keywords: Ananas comosus; Internal darkening; Storage